Empowering adult learners through interdisciplinary and inclusive digital recognition of prior learning in higher education - Rambharose, Rekha (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Higher education in South Africa is undergoing a profound transformation driven by persistent socio-economic disparities, historical marginalisation, and the rapid expansion of digital technologies. Within this evolving landscape, Recognition of Prior Learning (RPL) serves as a pivotal mechanism to validate the experiential knowledge of adult learners—knowledge that is often marginalised within conventional academic frameworks. This study investigates how interdisciplinary curricula, digital platforms, and inclusive pedagogical practices can empower adult learners and enhance equitable access to academic participation. Anchored in experiential learning theory and decolonial pedagogy, the research employs a qualitative-dominant mixed-methods design, integrating qualitative learner narratives and practitioner reflections with quantitative data on engagement and completion. Findings reveal that digital RPL, when supported by tailored mentorship, equitable access strategies, and interdisciplinary integration, significantly fosters learner agency, professional identity transformation, and academic success. The study culminates in the development of the IDEAL-RPL Framework, an evidence-based, institutional model that operationalises epistemic justice, digital inclusion, and relational pedagogy. This contribution advances the Scholarship of Teaching and Learning (SoTL) by offering a holistic and transformative approach responsive to the demands of a decolonised, digital, and interdisciplinary higher education landscape.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 6, Volume 9, 2025
Keywords: Access; Higher education; Digital innovation; RPL; IDEAL-RPL Framework; Education; Education higher, South Africa; Recognition of prior learning -- South Africa; Adult education -- South Africa; Computer-assisted instruction